Estimación de los parámetros de la distribución Lambda generalizada a través del método de momentos y el programa MatLab. (2015)
Many of the problems in diﬀerent areas of knowledge can be solved through the construction of statistical models. Such models are commonly supported on probability distributions and exactly how the data are taken as the basis for its construction are distributed. Interest distributions adjusting data sets intended to describe their behavior by distributing found. The paper presents a family of these distributions, the Lambda widespread distribution (DLG) and a MatLab program implementing the method of moments to estimate the distribution parameters to ﬁt data sets or approaching some popular distributions.